The Concept of Qur'anic Communication from the Perspective of the Philosophy of Science - Kusnadi, Kusnadi; Rohmah, Siti; Akmal, Akmal; Suryadinata, M.; Arib, Juhrah M.; Mokodenseho, Sabil (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study aims to analyze the term al-ittishāl or al-mūashalah, specifically interpreted in Arabic as communication. The study addresses inquiries regarding the essence and existence of communication in the Qur'an from ontological, epistemological, and axiological perspectives. The focus of this study is crucial for analysis as the mainstream perception of communication in society has predominantly concentrated on aspects such as al-qaul, al-khitab, al-kalam, and the like. Employing thematic tafsir methodology, this research analyzes data primarily derived from the Qur'an, its exegesis, and hadith, while relevant books and journal articles serve as secondary sources. The research reveals that the essence of Qur'anic communication through the term al-ittishāl, stemming from the root word washala and its derivatives, recurs 12 times within the Qur'an across various chapters, all of which connote meanings of connection, seeking protection, reaching, and revelation (clarification). Meanwhile, the existence of communication in the Qur'an, from the perspective of the philosophy of science, is categorized into three aspects. Firstly, the ontological dimension of communication in the Qur'an is evident in the term yashilūna, signifying 'connected, linked, and reaching.' Secondly, the epistemological aspect of communication is depicted through its various forms within the Qur'an, encompassing verbal and non-verbal expressions, whether direct or indirect, unidirectional, or bidirectional. Thirdly, the axiological aspect of Qur'anic communication is discernible in its intended purpose or benefits, aiming for human understanding of the conveyed instructions and demonstrating the power of Allah.